Starvation-induced metabolic rewiring affects mTORC1 composition in vivo - Edgar Kaade; Simone Mausbach; Nina Erps; Marc Sylvester; Farhad Shakeri; Ron D. Jachimowicz; Volkmar Gieselmann; Melanie Thelen (Scientific Reports)
Abstract Lysosomes play a crucial role in metabolic adaptation to starvation, but detailed in vivo studies are scarce. Therefore, we investigated the changes of the proteome of liver lysosomes in mice starved short-term for 6h or long-term for 24h. We verified starvation-induced catabolism by weight loss, ketone body production, drop in blood glucose and an increase of 3-methylhistidine. Deactivation of mTORC1 in vivo after short-term starvation causes a depletion of mTORC1 and the associated Ragulator complex in hepatic lysosomes, resulting in diminished phosphorylation of mTORC1 target proteins. While mTORC1 lysosomal protein levels and activity in liver were restored after long-term starvation, the lysosomal levels of Ragulator remained constantly reduced. To determine whether this mTORC1 activity pattern may be organ-specific, we further investigated the key metabolic organs muscle and brain. mTORC1 inactivation, but not re-activation, occurred in muscle after a starvation of 12 h or longer. In brain, mTORC1 activity remained unchanged during starvation. As mTORC1 deactivation is known to induce autophagy, we further investigated the more than 150 non-lysosomal proteins enriched in the lysosomal fraction upon starvation. Proteasomal, cytosolic and peroxisomal proteins dominated after short-term starvation, while after long-term starvation, mainly proteasomal and mitochondrial proteins accumulated, indicating ordered autophagic protein degradation.